Perceptions of Organizational Politics Research: Past, Present, and Future - Hochwarter, Wayne A.; Rosen, Christopher C.; Jordan, Samantha L.; Ferris, Gerald R.; Ejaz, Aqsa; Maher, Liam P. (Journal of management, 2020)
Research examining the influence of perceptions of organizational politics (POPs) is currently at a nexus—capable of recognizing its previous contributions but also with an eye toward the future. Scholars credit much of the maturation over the past 30 years to Ferris, Russ, and Fandt’s seminal model. Despite the ever-increasing number of publications attributed to this topic, and model, opportunities to bridge and expand the current research base remain plentiful. We begin this review by differentiating POPs from political behavior and constructs considered overlapping conceptually. We then describe the evolution of two models responsible for guiding POPs research and conclude our review by summarizing meta-analytic studies investigating antecedents and outcomes of POPs. Doing so allows us to identify gaps currently impeding development and to recommend relevant approaches to extend research. Following this review, we introduce event systems theory as a guiding framework for integrating and expanding the knowledge base. This structure allows scholars to recast POPs as a discrete phenomenon capable of being evaluated in terms of its novelty, disruption, and criticality. Theoretically, this approach allows for greater precision in identifying causes and consequences of POPs, and it provides insight into how such perceptions emerge and evolve. Last, we discuss future research opportunities intended to improve understanding of this pervasive phenomenon, and we encourage much-needed future research examining the dynamics of POPs in contemporary work settings.